Maternal Hyperuricemia in Normotensive Singleton Pregnancy, a Prenatal Finding with Continuous Perinatal and Postnatal Effects: Maternal Hyperuricemia in Normotensive Singleton Pregnancy - Saleem, Hafiza Asifa; Zainab, Sadia; Uzma, Syeda; Hayat, Naheed; Azhar, Maheen; Shaheen, Nabila (Pakistan Journal of Health Sciences, 2025)
Maternal hyperuricemia has been associated with various adverse pregnancy outcomes in hypertensive disorders, but its effects in normotensive singleton pregnancies remain unclear. Objective: To assess the impact of maternal hyperuricemia on perinatal and postnatal outcomes in normotensive singleton pregnancies, with a focus on birth weight, gestational age, NICU admissions, and gestational anemia. Methods: This study was conducted at the Department of Obstetrics and Gynecology, Tertiary Care Hospital, Bahawalpur city, from 30-11-2022 to 29-06-2023. The Study Design was prospective observational cohort study. A cohort of normotensive pregnant women was prospectively followed to assess the association between maternal hyperuricemia and perinatal as well as postnatal outcomes. Results: Significant differences were observed in birth weight and gestational age between hyperuricemic and normouricemic mothers. Infants born to normourecemic mothers had higher birth weights (3.80 ± 0.35 kg vs. 3.51 ± 0.40 kg, p = 0.015) and were delivered earlier (38.50 ± 1.20 weeks vs. 39.35 ± 1.00 weeks, p = 0.025). Additionally, hyperuricemic mothers showed a higher prevalence of NICU admissions (42.9% vs. 26.5%, p = 0.035) and gestational anemia (42.9% vs. 19.1%, p = 0.043). Logistic regression revealed that maternal uric acid levels significantly influenced the likelihood of NICU admissions, suggesting a complex interaction with perinatal outcomes. Conclusions: Maternal hyperuricemia in normotensive singleton pregnancies significantly influences birth weight, gestational age at delivery, NICU admission rates, and the prevalence of gestational anemia, indicating a notable clinical impact in this population.